2022
DOI: 10.1111/srt.13189
|View full text |Cite
|
Sign up to set email alerts
|

Facial skin characteristics and concerns in Indonesia: A cross‐sectional observational study

Abstract: Background Facial skin characteristics and appearance vary according to ethnicity. While much of this knowledge is derived from the Caucasian population, lately there have been efforts to gain such understanding in various regions in Asia.  In this paper, we have built an understanding of such features in Indonesia. In Indonesia, a section of females wears a traditional veil (hijab) to cover the scalp and part of face. The influence of the hijab on facial skin attributes was also investigated. Methods In a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
3
4
0
1
Order By: Relevance
“…Based on images generated by several thousand Skinly users at home this evenness algorithm determined a decrease in general evenness of cheek skin with rising age. These results are in line with data from the literature 40 . At home measurements with the Skinly device showed that Thiamidol treatment lightened skin tone and improved the evenness of cheek skin.…”
Section: Discussionsupporting
confidence: 91%
“…Based on images generated by several thousand Skinly users at home this evenness algorithm determined a decrease in general evenness of cheek skin with rising age. These results are in line with data from the literature 40 . At home measurements with the Skinly device showed that Thiamidol treatment lightened skin tone and improved the evenness of cheek skin.…”
Section: Discussionsupporting
confidence: 91%
“…also observed a reduced facial cheek elasticity and collagen with an increase in melanin content among elder Malaysian women. Similar evaluation by Du et al 77 . also reported that Indonesian women in Jakarta showed a decrease in skin elasticity (R2 and R7), TEWL and sebum (forehead) as well as a higher pore severity on the cheek, especially after 50 years.…”
Section: Biophysical Properties Of Asian Skinsupporting
confidence: 77%
“…also observed a reduced facial cheek elasticity and collagen with an increase in melanin content among elder Malaysian women. Similar evaluation by Du et al77 also reported that Indonesian women in Jakarta showed a decrease in skin elasticity (R2 and R7), TEWL and sebum (forehead) as well as a higher pore severity on the cheek, especially after 50 years. The same report also observed age-dependent changes on skin colour including an increase in lightness and a decrease in redness at forehead after 40 years, a decrease in lightness and an increase in yellowness at the cheek after 50 years.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Generally, skin smoothness is negatively correlated with age; however, our experimental results confirm that there is no significant correlation between this and age, which is the same as the known findings. 25 However, wrinkles show a significant increase, with a strong correlation with age, 26 suggesting that there is no significant correlation between the smoothness of the skin and the amount of wrinkles. In addition, we found that sebum content, the most important component in maintaining skin barrier function, decreased rapidly with age, with a decrease of more than 70% in the oldest ancestors compared to the youngest group (Figure 1), and there was a significant moderate intensity correlation between sebum content and age (Figure 2, R = −0.504), which is consistent with the results of several other studies.…”
Section: Skin Parameters and Agementioning
confidence: 99%